U.S. MIDDLE EASTERN POLICY: NEW APPROACHES AND OLD PROBLEMS - KARYAKIN, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2010)
In the last decade, when operating outside its borders, the United States has mainly been opposing the geopolitical challenges President Obama inherited from his predecessor; this is primarily true of the Middle East.From the very beginning, the president-elect outlined America’s political priorities in this volatile region of the world. He shifted the accents from ending the war in Iraq to Afghanistan where he promised to increase his country’s military contingent, strengthen the law-enforcement and administrative structures and involve Pakistan in the anti-Taliban struggle.The Iranian nuclear file was treated as another serious threat to U.S. security. The interconnected threats called for adequate measures; as a first step, President Obama appointed Richard Holbrooke his Special Representative for Afghanistan and Pakistan; George Mitchell, Special Envoy for the Middle East, and Dennis Ross, advisor on Iran.This and considerable funding of military and other spheres did nothing to make Washington’s Middle Eastern policy more consistent; so far it remains ambiguous in the Iranian vector as well. During 2009, for example, Washington twice changed its mind about the numerical strength of its military contingent in Afghanistan; an announcement about its increase was followed by a decision to pull out in 2011. This shows that the incumbent president is trying to resolve this strategically important problem before the end of his presidential term. The Administration still has no idea about how to achieve “correct” relations with Islamabad, even though the situation in Afghanistan and Pakistan calls for interrelated policies to be pursued on both sides of their common border.In 2009-2010, the situation in Iraq stabilized to the extent that in the last days of George W. Bush’s presidency, his Administration announced that a gradual troop withdrawal was not far away.The events of 2009 and the first half of 2010, however, showed that security in Iraq is fragile to say the least and, without an acceptable domestic political balance, it will continue deteriorating until the day of America’s final pull-out (sometime in 2011) arrives.American diplomacy has failed to make any perceptible progress on the Iranian nuclear issue; the crisis will escalate, which will probably force President Obama to make consequential political decisions.Washington’s efforts to settle the Palestinian-Israeli conflict and, in particular, to hold talks with Israel about the Jewish settlements fell through together with the illusions about America’s ability to succeed.So far, Barack Obama’s Cairo Speech can be described as the only triumph of America’s Middle Eastern policy. Speaking at Cairo University, the president said in particular: “I have unequivocally prohibited the use of torture by the United States, and I have ordered the prison at Guantanamo Bay closed by early next year.” And further: “I’ve come here to Cairo to seek a new beginning between the United States and Muslims around the world;” he assured the audience that his Administration had dropped the term “war on terror” coined by the previous administration.This did nothing to improve America’s image around the world; sociological polls in ProAmerica countries (Egypt, Jordan, Pakistan, and Turkey) revealed that the approval rate had dropped below 30 percent.It should be said in all justice that new approaches to Afghanistan, Pakistan, and Iran remained pending not only because the problems inherited from the previous administration defied resolution, but also because the world financial and economic crisis complicated the situation at home.